Connecting campus and community - mixed-use development at Nova Southeastern University - Champlin, Jon (Kansas State University, 2010)
College campuses are places of education and innovation for students, faculty, and the community of which they are a part. Universities have a unique opportunity to serve as the premier catalyst for development, which gives them the power to create new communities that are more than educational facilities. Nova Southeastern University, in Davie, Florida, is one such institution. The project site is 30 acres in the southwest corner of Nova’s campus. The blighted and disconnected strip mall currently composing the site will transform into an integrated and diverse mixed-use development that acts as a thriving icon for the university and surrounding community. Program elements included in the project are a medical research center, a library/bookstore, a hotel, retail, office, entertainment, and residential. Enhancing the social network of the university and community on one site, while creating a sense of place, is the design’s priority. Making an informed connection between theory and practice in landscape architecture, planning, and design is what gives this project validity. The design solution is a product of research, precedent studies, regional and site specific inventory and analysis, and client and personal goals. Integration between the campus and community is achieved by three design principles: 1) Place Making, 2) Connections, and 3) Community. These design principles establish and inform the social, physical, and natural systems at work in the design, as well as the user experience. A welcoming, comfortable, exciting, and iconic environment is created through the character of the place by attracting people to the site through place making. Connections are made between the site and the existing campus, the surrounding community, and the site users by physical layout and relationships. Program elements, dimensions, spatial ratios, building type, and shared amenities all exploit interaction and instill a sense of community. Each design principle is interconnected with the others, enhancing and enforcing the design as a whole.
Keywords: Mixed-Use; Campus; Community; Place Making; Connections; Landscape Architecture (0390)